2008
DOI: 10.1128/jvi.02723-07
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus DNA Ligase Recruits Cellular Topoisomerase II to Sites of Viral Replication and Assembly

Abstract: Vaccinia virus replication is inhibited by etoposide and mitoxantrone even though poxviruses do not encode the type II topoisomerases that are the specific targets of these drugs. Furthermore, one can isolate drugresistant virus carrying mutations in the viral DNA ligase and yet the ligase is not known to exhibit sensitivity to these drugs. A yeast two-hybrid screen was used to search for proteins binding to vaccinia ligase, and one of the nine proteins identified comprised a portion (residue 901 to end) of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 37 publications
3
40
0
Order By: Relevance
“…We found that knockdown of Nup62 inhibited the production of infectious VACV in a one-step growth experiment, but had no effect on entry and only modest effects on DNA replication and early and late viral gene expression. In addition, Nup62 knockdown did not prevent the previously reported association of cellular topoisomerase II with viral factories (34). However, TEM revealed a severe block in VACV morphogenesis beyond the IV stage.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We found that knockdown of Nup62 inhibited the production of infectious VACV in a one-step growth experiment, but had no effect on entry and only modest effects on DNA replication and early and late viral gene expression. In addition, Nup62 knockdown did not prevent the previously reported association of cellular topoisomerase II with viral factories (34). However, TEM revealed a severe block in VACV morphogenesis beyond the IV stage.…”
Section: Discussionmentioning
confidence: 75%
“…Cellular topoisomerase II, which is present predominantly in the nucleus, associates with the VACV DNA ligase in cytoplasmic viral factories (34). Localization of topisomerase II with viral factories was not prevented by knockdown of Nup62 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, that result relates to our current finding that the cellular DNA replication proteins FAM111A and RFC are host factors that restrict replication of the SPI-1 mutant. Thus far, investigations of poxvirus DNA replication have focused on viral proteins, except to show that cellular topoisomerase II is recruited by the viral DNA ligase to sites of viral DNA replication (30) and that cellular DNA ligase 1 can substitute for the viral ligase (29). At this time we can only suggest a speculative model for the roles of SPI-1, IRF2, FAM111A, and RFC3 in host restriction of poxviruses that may be useful for designing further studies (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Barrier-to-autointegration factor is an example of a host DNA-binding protein that inhibits VACV replication unless inactivated by the poxvirus B1 kinase (28). No cellular proteins essential for poxvirus DNA replication have been identified, although DNA ligase 1 can substitute for the VACV DNA ligase (29) and topoisomerase II is recruited to sites of viral DNA replication (30).…”
Section: Significancementioning
confidence: 99%
“…Additional experiments suggest that this virus-host PPI plays a positive role in promoting viral growth and perhaps contributes to the virulence of VACV in neural cells (109). Finally, a Y2H screen was used to investigate protein binding partners of VACV ligase (the A50R gene), and one of the nine host proteins identified was human topoisomerase II (95). This particular interaction was further confirmed by coimmunoprecipitation methods that showed that native ligase and a Flagtagged recombinant protein form complexes with human topoisomerase II in virus-infected cells (95).…”
Section: Virus-host-interacting Partnersmentioning
confidence: 99%